ANALISIS KETERAMPILAN SISWA DALAM MEMBUAT KARANGAN TEKS NARASI KEMERDEKAAN KELAS V SD NEGERI 08 PALEMBANG - Ina Chaerani; Destiniar, Destiniar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research discusses the analysis of narrative writing skills in the fifth grade at SD Negeri 8 Palembang for the academic year 2024. This study employs a qualitative descriptive research method using interview techniques and documentation studies. The validity test for this research includes source triangulation and data collection techniques. The data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. The results of the study indicate that fifth-grade students at SD Negeri 8 Palembang have adequate writing skills. The average assessment for each aspect is as follows: content organization with an average of 2.45 (adequate), grammar aspect with an average of 2.5 (adequate), word choice aspect with an average of 2 (adequate), and spelling and punctuation aspect with an average of 1.7 (poor).